Evidence for a thoracic crop in the workers of some Neotropical Pheidole species (Formicidae: Myrmicinae). (November 2020) - Casadei-Ferreira, A.; Fischer, G.; Economo, E.P.
Abstract: The ability of ant colonies to transport, store, and distribute food resources through trophallaxis is a key advantage of social life. Nonetheless, how the structure of the digestive system has adapted across the ant phylogeny to facilitate these abilities is still not well understood. The crop and proventriculus, structures in the ant foregut (stomodeum), have received most attention for their roles in trophallaxis. However, potential roles of the esophagus have not been as well studied. Here, we report for the first time the presence of an auxiliary thoracic crop in Pheidole aberrans and Pheidole deima using X-ray micro-computed tomography and 3D segmentation. Additionally, we describe morphological modifications involving the endo- and exoskeleton that are associated with the presence of the thoracic crop. Our results indicate that the presence of a thoracic crop in major workers suggests their potential role as repletes or live food reservoirs, expanding the possibilities of tasks assumed by these individuals in the colony. Our contribution emphasizes the utility of combining data from external and internal morphology to better understand functional and behavioral mechanisms. Highlights: 2D and 3D imaging are used to investigate the esophagus anatomy in Pheidole . First record of a thoracic crop in workers of Neotropical Pheidole species. Major workers have a potential role as repletes or live food reservoirs due to the thoracic crop. Pro- and mesothorax shape provide an increase in the mesosomal cavity in which the esophagus expands as an auxiliary crop.